2016
DOI: 10.1186/s13104-016-2247-4
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae among suspects of sexually transmitted infection in Gambella hospital, Ethiopia: risk factors and drug resistance

Abstract: BackgroundNeisseria gonorrhoeae is a bacterium responsible for one of the classic sexually transmitted infection (STI) gonorrhea. Antibiotic resistant strains are emerging at alarming rate. Multiple sexual partners, unsafe sex and substance use habits are the main host related risk factors for acquiring the infection. Thus, this study aimed at determining the magnitude, its determinants and antimicrobial resistance profile of N. gonorrhoeae in a place where there is risk related cultural practices and relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
28
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 14 publications
13
28
10
1
Order By: Relevance
“…The antimicrobial resistance patterns ranged from 7(28%) for Cefotaxime and Clindmycin up to 100% in Tetracycline. This Tetracycline resistance pattern was similar with the study done in Gambella hospital, Ethiopia [ 1 ]. The present study showed a high level of resistance to Tetracycline 25(100%) and Ciprofloxacin 13(52%) compared to the study done in North West Ethiopia (92.6, 40.9%) (15), Southern Ethiopia (55, 18%) [ 2 ] and United States (25.3, 19.2%) [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The antimicrobial resistance patterns ranged from 7(28%) for Cefotaxime and Clindmycin up to 100% in Tetracycline. This Tetracycline resistance pattern was similar with the study done in Gambella hospital, Ethiopia [ 1 ]. The present study showed a high level of resistance to Tetracycline 25(100%) and Ciprofloxacin 13(52%) compared to the study done in North West Ethiopia (92.6, 40.9%) (15), Southern Ethiopia (55, 18%) [ 2 ] and United States (25.3, 19.2%) [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…Neisseria gonorrhoeae is a Gram negative, coffee-bean shaped intracellular diplococcus bacterium responsible for gonorrhoea which is one of the classical sexually transmitted infections (STIs) [ 1 ]. The causative organism is highly adapted to the genital tract and often causing asymptomatic and undetected infection [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall yield of N. gonorrhea isolates of 4.9% in the whole study population is lower than that found in studies conducted elsewhere in some African countries; 11.3% and 5.1% in Ethiopia, 8.4% in Tanzania, 42% in Bangladesh, 59% in Uganda and 80% Malawi. [17][18][19][20][21] The variation in prevalence rates in those other studies compared to the current study may be due to differences in the study population where pregnant women with urethral discharges attending antenatal clinics in Uganda, the antiretroviral therapy follow up cases in Ethiopia, patients only with urethral discharge in STI clinics in Malawi, and commercial sex workers in Bangladesh.…”
Section: Prevalence Of Neisseria Gonorrhea Infection and Sociodemogramentioning
confidence: 99%
“…This finding is in concordance with studies conducted in some parts of Africa. 17,18 Although we never looked for factors influencing propensity to N. gonorrhea infection, some studies have reported sexual promiscuity of males as they tend to have more sexual partners compared to their female sexual counter parts. 27 Besides, by nature males are more symptomatic for the infection than their female counterparts.…”
Section: Sociomentioning
confidence: 99%